Community resilience to health emergencies: a scoping review - Eng-Kiong Yeoh; Steve Milanese; Beena E Thomas; Hayley MacGregor; Janine Dizon; Sharon Abramowitz; Nina Gobat; Luisa Enria; Daniel H de Vries; Gisela van Kessel; Doris Burtscher; Rim Kwang; et al. (BMJ Global Health)
Background There is recognition of the importance of community resilience in mitigating long-term effects of health emergencies on communities. To guide policy and practice, conceptual clarity is needed on what community resilience involves and how it can be operationalised for community protection in ways that empower and strengthen local agency.Objectives To identify the core components of community resilience to health emergencies using a scoping review methodology.Search methods PubMed, EMCARE, Scopus, Web of Science, PTSDpubs, APO and ProQuest Dissertations were systematically searched to identify review studies published from 2014.Selection criteria Studies were included if they reported a review of original research papers investigating community resilience in the context of a health emergency.Data collection and analysis Data were extracted from included studies using a specially developed data extraction form. Qualitative data were subjected to a meta-synthesis consisting of three levels of analysis.Main results 38 evidence reviews were included. Analysis identified recurring characteristics of community resilience. Six studies reported 10 abilities required for community resilience including: adapt, transform, absorb, anticipate, prepare, prevent, self-organise, include, connect and cope. 25 studies reported 11 types of resources: social, economic, environmental, governance, physical infrastructure, institutional, communication, human capital, health, emergency management and socioeconomic.Conclusions 21 components have been identified that can be used as a basis for operationalising and measuring community resilience. In contexts of disaster management, community resilience is a fairly mature concept that reflects a community’s inherent capacity/abilities to withstand and recover from shocks. There is a need to incorporate a ‘resource’ perspective that speaks to a wider enabling environment. There is scope to investigate whether the same set of components identified here has relevance in public health emergencies emanating from disease or human acts of aggression and to articulate resilience logics to critical endpoints for health emergency management.